Equality as an ethical concept within the context of nursing care rationing - Papastavrou, Evridiki (Nursing philosophy, 2020)
The concept of equality is subject to many different interpretations, and it is closely connected to similar concepts such as equity, justice, fairness, and human rights. As an ideal, equality entails many aspects that are untenable. For instance, genetic and social inequalities may never be extinct, but they can both be ameliorated by proper distribution of society's resources. Likewise, within the context of health care, equality can be promoted by proper rationing of health resources, amongst which nursing care stands out. In the field of nursing, the principle of equality presents itself in various forms of ethical and deontological mandates. However, beyond good intentions and abstract notions, there is a need to examine the ways in which nurses enforce this principle in practice, within the reality of modern health systems. Although there is scarcity of qualitative evidence in the nursing care rationing literature, existing studies suggest that fair treatment pertains to a largely intuitive sense of equality which involves subjective perceptions and judgements about rationing. Nurses’ initial predisposition is to view all patients as equal and treat them in an equal manner; yet, on an individual basis, each patient has a different starting point, different needs and different prospects that render rationing decisions complex and uncertain. Equality should be accepted with its unavoidable limitations in practice and be further examined within the context of nursing care rationing, in the hope that it can be advanced in a consistent way, despite the idealistic nature in many of its aspects.